Digital Literacy Training: Canva Application in Strengthening Women's Entrepreneurship in Ngenep Village Karangploso District Malang Regency - Savitri, Intan Dewi; Khotimah, Siti Khusnul; Rusmawati, Roosi (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aimed to address the impact of Covid-19 and government policies on women's creativity and entrepreneurship in Ngenep Village, Karangploso, Malang Regency. Specifically, it focused on enhancing digital literacy through Canva application training to support women entrepreneurs in promoting their products effectively. Method: The study employed a community-based approach, conducting training sessions on digital literacy utilizing Canva. Data on participants' competence and subsequent sales were collected and analyzed to measure the effectiveness of the training. Practical Applications: The findings underscore the importance of digital literacy in empowering women entrepreneurs, particularly during crises like the Covid-19 pandemic. The training equips them with practical skills to promote their products, thereby enhancing their economic resilience and contributing to community development.Conclusion: The research highlights the pivotal role of digital literacy training, using tools like Canva, in supporting women's entrepreneurship in rural areas. By improving promotional capabilities, women entrepreneurs in Ngenep Village can potentially increase sales and positively impact their communities' economic well-being.